1998
DOI: 10.1007/s002449900382
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity and Pathogenicity Testing of the Insect Pest Control Fungus Metarhizium anisopliae

Abstract: Renewed interest in the use of Metarhizium anisopliae and its toxins for insect control prompted the following safety assessment. A neutral extract (methylene chloride, pH 7.2), derived from M. anisopliae cultures, was evaluated for toxicity and mutagenicity using aquatic animal bioassays and the Ames test. The average LC50 of the neutral extract obtained in static, acute 96-h tests conducted with Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 17 publications
0
19
0
1
Order By: Relevance
“…Given this effect, it is appealing to consider that serinocyclins may play a protective role for the fungus in aquatic or highly humid environments since the compounds themselves are hydrophilic. For example, M. anisopliae ARSEF 2575 conidia have been reported to cause the death of embryos of inland silverside fish and grass shrimp (26,27) in safety assessments evaluating effects on nontarget organisms. How the behavioral effect of serinocyclin A on mosquito larvae relates to its role in the biology of M. anisopliae as a soil and plant-associated saprophyte and insect pathogen is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Given this effect, it is appealing to consider that serinocyclins may play a protective role for the fungus in aquatic or highly humid environments since the compounds themselves are hydrophilic. For example, M. anisopliae ARSEF 2575 conidia have been reported to cause the death of embryos of inland silverside fish and grass shrimp (26,27) in safety assessments evaluating effects on nontarget organisms. How the behavioral effect of serinocyclin A on mosquito larvae relates to its role in the biology of M. anisopliae as a soil and plant-associated saprophyte and insect pathogen is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been reported that the fungus may cause human keratitis (DeGarcia et al 1997). Other work has shown that the fungus can cause significant mortality of shrimp, frog and fish embryos exposed to conidia (Genthner et al 1994(Genthner et al , 1998. The latter effects, however, were not revealed in earlier studies where guppies, exposed to massive amounts of conidia, were not affected for periods up to two months (Roberts 1974).…”
Section: Metarhiziummentioning
confidence: 97%
“…Metarhizium anisopliae is such a fungal pathogen (Genthner et al 1998 and references therein; Vilcinskas and Götz 1999) that has previously been isolated from many insects, including a number of species of Atta leaf-cutting ants (Humber 1992). M. anisopliae hyphae penetrate the cuticle by a combination of physical forces and the secretion of enzyme complexes (Hajek and St. Leger 1994;Boucias and Pendland 1998;Vilcinskas and Götz 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Beauveria bassiana) have been extensively investigated for their usefulness as biological agents in insect pest control as an alternative to chemical insecticides (e.g. Diehl-Fleig et al 1988, 1993Genthner et al 1998;Jaccoud et al 1999;Vilcinskas and Götz 1999).…”
Section: Introductionmentioning
confidence: 99%